PENGARUH PENERAPAN STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK TERHADAP KUALITAS LAPORAN KEUANGAN - Agustami, Silviana; Agus Suintri, Imam (Jurnal Riset Akuntansi dan Keuangan, 2013)
This study aims to (1) determine the implementation of SAK ETAP at BPR in the Bandung city (2) determine the quality of the financial reports of BPR in the Bandung city, and (3) determine the effect of the implementation of SAK ETAP to quality financial reports on BPR in Bandung city. In this study, researchers used primary data for variable implementation of SAK ETAP and the quality of financial reporting through questionnaires distributed to 11 BPR in the Bandung city. The method used in this research is descriptive method verikatif. The statistical analysis tools in this study using Spearman rank correlation to determine the direction and strength of the relationship between the two variables, while the coefficient of determination is used to determine the ability of the independent variable (X) in influencing the dependent variable (Y). These results indicate (1) the implementation of SAK ETAP at BPR in the Bandung city in general has been implemented adequately (2) BPR in the Bandung city has been preparing and presenting the financial statements sufficient to satisfy the elements of relevant, reliable, able to comparable, and understandable (3) the implementation of SAK ETAP moderate effect on the quality of the financial reports of BPR in the Bandung city, amounting to 0.587. Based on the calculation of the coefficient of determination SAK ETAP implementation contribute to or influence by 34.5%% of the quality of financial reporting at BPR in the Bandung city, while the remaining 65.5% was contributed by other factors not examined